ISCHEMIC OPTIC NEUROPATHY AS A COMPLICATION OF HEMODIALYSIS - (:unkn) unknown (WICHTIG EDITORE, 1995)
Optic neuropathy is one of a number of ocular complications occurring in patients with end-stage renal failure receiving hemodialysis. Optic neuropathy may result from uremia or ischemia. We describe the case of a patient with sequential loss of vision in each eye occurring whilst on hemodialysis and associated with hypotension. We postulate an ischemic etiology for this patients blindness.
Keywords: UREMIC OPTIC NEUROPATHY; ISCHEMIC OPTIC NEUROPATHY; HEMODIALYSIS COMPLICATION